The Analysis of Manganese (Mn) in Waste Water Treatment (IPAL) of Coal Mine of PT Bukit Asam Indonesia - Getari Kasmiarti; Rona Ayu Sakinah; Bambang Yudono (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2021)
Wastewater from the coal mining process containing heavy metal manganese is bad for water body and health of living things around it.  The South Sumatra Governor Regulation states that the content of iron (Fe) and manganese (Mn) must contain a maximum total of 7 mg/L and 4 mg/L before being released into the environment. This study aimed to verify the total dissolved Mn analysis method. Thirty-four (34) samples from the wastewater treatment plant pond were digested and measured by the Atomic Absorption Spectrophotometer (AAS) at a wavelength of 279.5 nm.  The analyzes performed were the precision, sensitivity, linearity, LOD detection limits and LOQ quantization limits. The measurement results showed the parameter value for a precision of 1.562%; linearity (coefficient of determination) standard curve 0.9939; sensitivity 0.0375; LOD 0.4287 g/mL; and LOQ 1.4291  g/mL. In conclusion, the measurement data for the total dissolved manganese met the quality standards for wastewater stated in the Regulation of the Governor of South Sumatra No.8 of 2012 by applying the predetermined method.